Letter: immunogenicity of infliximab originator vs. CT‐P13 in IBD patients. Issue 9 (11th October 2017) - Fiorino, G.; Correale, C.; Radice, S.; Allocca, M.; Furfaro, F.; Gilardi, D.; Nagore, D.; Del Rio, L.; Pascual, J.; Martínez, A.; Danese, S.
Abstract : This article is linked to Komaki et al papers. To view these articles visithttps://doi.org/10.1111/apt.14274 andhttps://doi.org/10.1111/apt.13990 .